The New Pathway: luci e ombre del progetto di riforma in materia di gestazione per altri nel Regno Unito (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This article considers the current legal regulation of surrogacy in the United Kingdom and examines the Law Commissions’ provisional proposals for the reform of the law of surrogacy. Over the past years, Family courts case-law pointed out that the requirements to obtain parental orders are restrictive and outdated. Having identified gaps and inconsistencies in the present regulatory framework, the article considers the proposals formulated in the consultation paper on surrogacy reform, mainly focusing on the “new pathway”. The provisional proposals appear to be aimed at better sup-porting the child, surrogates, and intended parents. However, this paper argues that some issues remains unresolved, such as the safeguard of new families and international surrogates.
Keywords: Biolaw; surrogacy; reform; parenthood; best interests